Pengaruh Bimbingan Kelompok dengan Teknik Role Playing dalam Meningkatkan Pemahaman Pelecehan Seksual - Ervira Damayanti; Rochani Rochani; Arga Satrio Prabowo (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2023)
This study aims to determine the effect of group guidance using role playing techniques in increasing knowledge of sexual harassment in grade VII students at SMPN 1 Cikeusik. This study used a quasi-experimental design method. The population of this study was 68 grade VII students at SMPN 1 Cikeusik, with a total sample of 10 students with 6 students as the control group and 4 students as the experimental group which were taken through purposive sampling technique. The research instrument used was a multiple choice questionnaire with a Guttman scale. Based on the Mann-Whitney U test showing the Asymp.Sig.(2-tailed) value of 0.010 <0.05, it can be concluded that